2021
DOI: 10.1113/jp281482
|View full text |Cite
|
Sign up to set email alerts
|

Local recovery of cardiac calcium‐induced calcium release interrogated by ultra‐effective, two‐photon uncaging of calcium

Abstract: In cardiac myocytes, subcellular local calcium release signals, calcium sparks, are recruited to form each cellular calcium transient and activate the contractile machinery  Abnormal timing of spark recovery after their termination may contribute to arrhythmias  We developed a method to interrogate recovery of calcium spark trigger probabilities and their amplitude over time using two photon photolysis of a new ultra-effective caged calcium compound  The findings confirm the utility of the technique to defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Ca 2+ release refractoriness, measured using the ratio of the second:first Ca 2+ spark occurring from the same CRU using a chemical modification of RyR2 with low concentration ryanodine [ 104 ], was reduced in a transgenic mouse model of the GoF CPVT-causing RyR2-R420Q +/− mutation under both basal and isoproterenol stimulation, indicating increased CICR sensitivity [ 105 ]. Reduced refractoriness was also observed in the same RyR2 CPVT model using two-photon photolysis of a caged Ca 2+ chelator [ 106 ] and in other models of GoF CPVT due to missense mutations (CSQ2-R33Q [ 107 ]) or knockout of CSQ2 [ 108 ].…”
Section: Arrhythmogenic Consequences Of Ryr2 Dysfunctionmentioning
confidence: 79%
“…Ca 2+ release refractoriness, measured using the ratio of the second:first Ca 2+ spark occurring from the same CRU using a chemical modification of RyR2 with low concentration ryanodine [ 104 ], was reduced in a transgenic mouse model of the GoF CPVT-causing RyR2-R420Q +/− mutation under both basal and isoproterenol stimulation, indicating increased CICR sensitivity [ 105 ]. Reduced refractoriness was also observed in the same RyR2 CPVT model using two-photon photolysis of a caged Ca 2+ chelator [ 106 ] and in other models of GoF CPVT due to missense mutations (CSQ2-R33Q [ 107 ]) or knockout of CSQ2 [ 108 ].…”
Section: Arrhythmogenic Consequences Of Ryr2 Dysfunctionmentioning
confidence: 79%
“…Briefly, one RyR2 channel within a cluster is modified by a very low concentration of ryanodine. This channel is thought to drive a cluster which fires repetitive Ca 2+ sparks that are further studied in detail to evaluate the Ca 2+ sensitivity of CICR and the RyR2s [28,29]. 2 for additional details.…”
Section: Sensitivity Of Cicr Is Augmented In Cpvt Cardiomyocytes In B...mentioning
confidence: 99%
“…10 Questions of the angular dependence of the signal transmission efficiency are relevant to multiple signaling processes with particular examples of synaptic transduction 11 and could be especially important in the case of the so-called ''digital'' calcium signaling through ''calcium sparks'' displaying fine patterns in space and time. [12][13][14][15][16] A relatively new example of an angular-dependent capture process is regulation of mitochondrial voltage-dependent anion channel, VDAC, by its interaction with peripheral cytosolic proteins possessing disordered negatively changed tails. 17 It was shown that in this signaling mechanism the disordered tail is trapped by the channel whereas the rest of the protein body -its structured part -serves as a membranebound anchor.…”
Section: Introductionmentioning
confidence: 99%